All Days 2008
DOI: 10.2118/113993-ms
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Processes Responsible for Heavy Oil Recovery by Alkali-Surfactant Flooding

Abstract: This paper describes a suite of alkali-surfactant (AS) floods that were performed in systems containing viscous heavy oil (11,500 mPa⋅s). The study investigates how AS injection can be used to generate oil and water emulsions, which can in turn lead to improved sweep efficiencies and oil recovery. Data is obtained from core flooding, with in-situ saturation measurements made using low field NMR. This work is applicable to the many heavy oil reservoirs in countries like Canada and Venezuela that contain viscous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Recovery in chemical flooding of heavy-oil reservoirs have been shown to depend on flow rate, and consequently on the shear rate [5][6][7][8][9][10]. This is consistent with capillary number dependencies associated with emulsion flow [11].…”
Section: Evidence Of Emulsions Conformance Effects: Heavy-oil Eorsupporting
confidence: 66%
See 1 more Smart Citation
“…Recovery in chemical flooding of heavy-oil reservoirs have been shown to depend on flow rate, and consequently on the shear rate [5][6][7][8][9][10]. This is consistent with capillary number dependencies associated with emulsion flow [11].…”
Section: Evidence Of Emulsions Conformance Effects: Heavy-oil Eorsupporting
confidence: 66%
“…The issue of mobility ratio or control arises because viscous water has much lower viscosity than heavy oil and consequently the displacement front develops fingers and oil recovery is generally poor. Alkali-surfactant (AS) flooding has been shown to be a potential viable technology for EOR in heavy-oil reservoirs [5][6][7][8][9][10]. However, in the absence of a thickening agent such as polymers, the increase in water saturation as water displaces oil only worsens the mobility control issue.…”
Section: Evidence Of Emulsions Conformance Effects: Heavy-oil Eormentioning
confidence: 99%
“…In these systems, which were expected to form only W/O emulsions, there was no difference between the response from high vs. low permeability cores in Table 5. This could potentially be an indication of wettability alteration (52) , but in general, it can be concluded that these emulsions are equally effective in all permeabilities for plugging off the water channels and providing improved sweep in the core. Thus, AS flooding is not only possible in reservoirs where fresh water is not available, but, in fact, may be more stable than fresh water chemical floods.…”
Section: Core Flood Experimentsmentioning
confidence: 99%
“…Alkali-surfactant-polymer flooding can allow operators to extend reservoir pool life and extract incremental reserves recently inaccessible by conventional EOR methods such as waterflooding (Jia et al, 2005). Chemical surfactants use to decrease the IFT between liquid and liquid phase, making the immobile oil mobile (Touhami et al, 1998;Bryan et al, 2008). Alkali decreases adsorption of the surfactant on the solid surfaces and reacts with acidic substances in the oil to form new surfactant.…”
Section: Microemulsion Floodingmentioning
confidence: 99%